Bandwidth Enhancement of a Bell-shaped UWB Antenna for Indoor Localization Systems - Karoui, M. S.; Ghariani, N.; Lahiani, M.; Ghariani, H. (Engineering, Technology & Applied Science Research, 2021)
In this paper, a simple method of enhancing the bandwidth of the Bell-shaped UWB Antenna for indoor localization systems is proposed. Therefore, a modified version of the bell-shaped Ultra-Wide Band (UWB) antenna for indoor localization systems is presented. The proposed antenna is printed on a low-cost FR-4 substrate of 21×27×1.6mm3 size. It is composed of a bell-shaped radiating patch and a multi-slotted ground plane. The measured results show that the proposed antenna has an impedance bandwidth of about 11.2GHz ranging from 3.16GHz to 14.36GHz at S11<−10dB. Compared to the original version, an enhancement of about 5.56GHz in the measured impedance bandwidth was observed.